Reading for a reason : - Blass, Laurie (McGraw-Hill, 2006)
The three-level series "Reading for a reason" focuses on cross-cultural content and promotes critical thinking skills. This Reading for a reason 1, the high beginning level student book, is the first in the theme-based reading series that lead students to develop the critical reading and vocabulary skills they need to become confident, academic readers.